29 Pre- and Post-Weaning Injections of Bovine Somatotropin to Optimize Puberty Achievement of Purebred Bos Indicus Beef Heifers. (1st March 2018) - Piccolo, M; Cappellozza, B I; Cooke, R; Mirando, M; Carvalho, R; Colombo, E A; Santili, F; Ferreira, V; Batista, L; Filho, R; Vasconcelos, J L M; Moriel, P
Abstract: This study evaluated the growth and puberty attainment of Nellore heifers administered recombinant bovine somatotropin (bST ) or saline injections during pre- and/or post-weaning phases. On d -7, 177 suckling Nellore heifers were stratified by age (80 ± 6 d), and randomly assigned, in a 2 × 2 factorial design (43 to 44 heifers/treatment), to receive injections of saline (5 mL 0.9% NaCl) or sometribove zinc (6.14 mg/kg of BW 0.75 ) during pre- (d 0 and 10; PRE ) and/or post-weaning phases (d 167 and 177; POS ). Heifers were managed as a single group in Brachiaria decumbens pastures from d 0 until 24 d post-weaning (d 191), and limit-fed a corn silage-based TMR for 189 d to achieve between 293 and 315 kg on d 380. Full BW (all heifers) and blood samples from jugular vein (15 heifers/treatment) were collected on d 0, 10, 167, 177, and monthly from d 191 to 380. Transrectal ultrasonography of ovaries was performed on d 1 and 10 of each month from d 229 to 380 to assess heifer puberty attainment. Liver samples were collected on d 0, 10, 167, 177, and 380 (10 heifers/treatment). No interactions among PRE, and POS injections of saline and bST were detected for any variable ( P ≥ 0.11). Pre-weaning bST injections increased heifer ADG from d 0 to 10 and plasma IGF-1 on d 10 ( P ≤ 0.03), did not impact ADG from d 0 to 177, plasma IGF-1 from d 259 to 380, and any liver gene mRNA expression ( P ≥ 0.19), but tended to decrease ADG from d 191 to 380 ( P = 0.07) and percentage of pubertal heifers on d 249, 359, and 380 ( P ≤ 0.07) compared to saline injections. Post-weaning bST injections increased plasma IGF-1 on d 177 and overall liver mRNA expression of GHR-1A ( P ≤ 0.05), decreased plasma IGF-1 from d 259 to 380 ( P = 0.03), tended to decrease liver mRNA expression of GHR-1B on d 177 ( P = 0.08), but did not impact ADG from d 167 to 177 and 191 to 380, and puberty attainment from d 229 to 380 ( P ≥ 0.12) compared to saline injections. Therefore, pre- and post-weaning bST injections successfully increased heifer plasma IGF-1 concentrations after 10 d of first injection. But, contrary to our hypothesis, post-weaning bST injections had no impact, whereas pre-weaning bST injections diminished puberty attainment of Nellore heifers compared to saline injections.